An Expanded Porphycene with High NIR Absorptivity That Stabilizes Two Different Kinds of Metal Complexes. Issue 10 (16th January 2018) - Anguera, Gonzalo; Cha, Won‐Young; Moore, Matthew D.; Brewster, James T.; Zhao, Michael Y.; Lynch, Vincent D.; Kim, Dongho; Sessler, Jonathan L.
Abstract: A new expanded porphycene with 26 π‐electrons has been prepared by the McMurry coupling of 1, 4‐bis(3, 4‐diethyl‐2‐pyrryl)benzene dialdehyde. Expansion of the porphycene framework provides a ligand capable of stabilizing a bis(rhodium) and a monoruthenium complex. These new porphycene derivatives absorb strongly in the NIR spectral region, with appreciable absorptivity up to 1300 nm. On the basis of their ground‐ and excited‐state spectroscopic features and structural parameters, both the free‐base system and the bis(rhodium) complex are considered to be Hückel‐type aromatic systems. This conclusion is supported by DFT calculations. Abstract : Expanded aromatics : An expanded porphycene prepared by a McMurry reaction from 1, 4‐bis(3, 4‐diethyl‐2‐pyrryl)benzene dialdehyde displays Hückel‐type aromaticity. It supports the formation of an aromatic bis(rhodium) complex (left) and a non‐aromatic, ring‐contracted, sandwich‐type monoruthenium complex (right).